The Reasons Behind the Failure of the European Supervision Order: The Defeat of Liberty Versus Security - Ana Maria Neira-Pena (European Papers, 2020)
(Series Information) European Papers - A Journal on Law and Integration, 2020 5(3), 1493-1509 | European Forum Insight of 4 November 2020 | (Table of Contents) I. Objectives of the European supervision order. - II. The failure in application of the European supervision order in the face of the success of the European arrest warrant. - III. The reasons for the failure in application of the ESO. | (Abstract) The European Supervision Order is an instrument of mutual recognition of judicial decisions essential to guarantee the exceptional nature of pre-trial detention. It also prevents discrimination of suspects and accused persons in criminal proceedings on grounds of nationality or residence, with regard to the possibilities of enjoying provisional release pending trial. It is, in short, an instrument that stands as a guarantee of the freedom of citizens in the European Area of Freedom, Security and Justice. However, despite its crucial role, the use of this instrument is very scarce, as its application encounters significant obstacles, including the insufficient level of trust between Member States, which appears to play a key role.